2009
DOI: 10.1007/s11605-009-0916-5
|View full text |Cite
|
Sign up to set email alerts
|

Very High Serum CA 19-9 Levels: A Contraindication to Pancreaticoduodenectomy?

Abstract: Patients who normalized their CA19-9 levels postoperatively had equivalent survival to patients with normal preoperative CA 19-9 levels. Preoperative serum CA 19-9 level by itself should not preclude surgery in patients who have undergone careful preoperative staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 25 publications
0
21
0
2
Order By: Relevance
“…Based on these findings, the authors recommended surgery in all patients with a BL tumor who at least did not progress while receiving preoperative treatment. It has been showed that CA 19-9 serum values can be predictive of the resectability status and overall survival in resectable and BL pancreatic cancer patients [24,25]. Two studies showed that in patients with BL pancreatic cancer treated with neoadjuvant chemotherapy, the failure to normalize CA 19-9 levels was an independent risk factor for lower overall survival after resection [7,26].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, the authors recommended surgery in all patients with a BL tumor who at least did not progress while receiving preoperative treatment. It has been showed that CA 19-9 serum values can be predictive of the resectability status and overall survival in resectable and BL pancreatic cancer patients [24,25]. Two studies showed that in patients with BL pancreatic cancer treated with neoadjuvant chemotherapy, the failure to normalize CA 19-9 levels was an independent risk factor for lower overall survival after resection [7,26].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these studies suggest that a median CA 19-9 serum level <100 U/ml correlates with resectability (41-80%) whereas levels >100 U/ml suggest advanced or metastatic pancreatic cancer (60-85%) (Table 3). The utility of serum CA 19-9 levels to provide meaningful prognostic information and permit patient stratification (survival groups) based on CA 19-9 serum level has been extensively evaluated [22,24,26,30,31,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] (Table 4). Waraya et al performed a multivariate analysis of factors predicting survival in 117 pancreatic cancer patients undergoing surgical resection and reported that a low preoperative CA 19-9 serum levels (28-30 U/ml) (p<0.0016, relative risk (RR), 2.16) and positive peripancreatic margin (p<0.04, RR, 1.62) independently predicted survival [46].…”
Section: Ca 19-9: Introductionmentioning
confidence: 99%
“…U/ml unit/milliliter, SD standard deviation, NA not available, R0 resection-microscopic margin tumor free, R1 resection-microscopic margins positive for tumor, R2 resection-macroscopic tumor left behind Author, Year N= CA 19-9 cut-off levels (U/ml) Median survival (months) 4 months in patients with a preoperative CA19-9 level >150 U/ml (N=64), compared to a median survival of 22.1 months in patients with a CA19-9 serum level ≤150 U/ml (N=45, p<0.012) [45]. Table 3 lists additional studies which have used various cut-off levels for pre-operative CA 19-9 serum levels in an effort to predict survival among pancreatic cancer patients [22,24,26,30,31,[36][37][38][39][40][41][42][43][44][45][46][47][48][49]. These studies support the conclusion that a normal (<37 U/ml) or low preoperative CA 19-9 serum level (<100 U/ml) correlates with early pancreatic cancer stage and independently predicts improved overall survival, whereas an elevated CA 19-9 serum levels (>100 U/ml) is associated with a poor prognosis.…”
Section: Ca 19-9: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that elevated CA 19-9 levels are associated with worse stage-specific survival and recurrence 13,3638. Postoperative CA 19-9 levels are thought to be a more accurate estimate of prognosis than those obtained prior to resection 36,37.…”
Section: Carbohydrate Antigen 19-9mentioning
confidence: 99%